(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the importance of terminology in international legal documents and the problems that arise in the process of interpretation. The effectiveness of international legal documents depends on the accuracy, uniformity and correct interpretation of the terminology used in them. The study employs comparative legal, linguistic-semantic, document analysis, case-study, and statistical methods. According to the results, 68% of international legal terms are in a state of partial equivalence, with the main causes of terminological disputes being context-dependent meaning shifts (35%) and interlingual linguistic differences (28%). Modal verbs (97%), legal constructions (85%), and culture-specific terms (78%), were identified as the most problematic groups. Terminological correspondence between different legal systems averages 45-67 percent. 42 percent of terminological errors are critical and can change the fundamental meaning of a document.